Cytotoxic selectivity of MJC0.3 and MJC0.5, acidic ribosome-inactivating proteins isolated from Mirabilis jalapa L. leaves against various cancer cell-lines - Sismindari Mae Sri Hartati, Adhyatmika Retno S. Sudibyo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2010)
Mirabilis jalapa L. contains basic (MJ30) and acidic (MJC) Ribosome-inactivating proteins (RIPs). Further purificationof MJC has been found two RIPs, MJC0.3 and MJC0.5. This study is aimed to prove the cytotoxic selectivity ofMJC0.3and MJC0.5against many cancer cell-lines and normal cell line. The two RIPs, MJC0.3and MJC0.5were testedtheir cytotoxic effect on 8 human cancer cell lines and normal cell using MTT assay compared with MJC protein.The highest cytotoxic activities of MJC0.3and MJC0.5were against EVSA-T followed by T47D, HeLa,WiDR, SiHa,Raji, NS1, andMCF7, with the IC50 of 59.3, 102.4, 162.9, 190.5, 249.5, and 304.5 μg/mL, respectively for MJC0.3and 32.8, 75.5, 86.0, 108.3, 346.7, and 220.06 μg/mL, respectively for MJC0.5. Based on these IC50 values,MJC0.3 and MJC0.5 were specific to EVSA-T and T47D, whereas they were not selective against Raji and SiHa(SI<10.0). It can be concluded that he acidic RIPs isolated from M. jalapa L. leaves was potential to be developedas anticancer agents for breast cancer.Key words: acidic RIPs – M. jalapa L.- cytotoxic selectivity - cancer cell lines.